Small groups and performance of village organizations in rural development programme of BRAC - Rafi, Mohammad; Ahmed, Shah Asad; Hossain, S. M. Alamgir; Haque, Md. Fazlul; Dus, Tapon Kumar (BRAC Research and Evaluation Division (RED), 2019)
BRAC's Rural Development Programme (RDP) fonns the village organizations (VO) by formulating their objectives precisely and by laying out explicitly the activities within it that the members comprising it need to carry out These activities are designed as such to make these supportive to the achievement of the VO objectives. On the other hand, small groups by helping the VO members in carrying out their responsibilities indirectly contribute to the achievement of the same. Based on these observations it was assumed that if the small groups were serious in enacting its responsibilities the VO activities would be well carried out and thus their objectives would be achieved. The objectives of this study were to (1) investigate the status of small groups in RDP VOs; (2) investigate the extent to which the small groups contribute to the performance of the V Os; and (3) investigate the causal mechanisms that helped/hindered the performance of the VOs. Altogether 239 VOs were randomly selected for observation in this study. The selection was made from those presently functioning and formed in between 1986 and 1996. The performance of these VOs were assessed in terms of certain activities supposed to be conducted by its members in the weekly VO meetings, i.e., (1) ringing the bell before meeting starts, (2) attending the meeting, (3) starting the meeting on time, (4) reciting the 18 promises in the beginning of the meeting, ( 5) sitting by small groups, ( 6) depositing savings, (7) repaying the weekly loan installment, (8) following the repayment procedure, and (9) preparing resolution of the loan verbally requested for from the RDP office.